Les petites villes : des agents d’urbanisation durable ? - Marie-Eve Férérol (Territoire en Mouvement)
The objective of this article is to focus on the small towns and their role in the urbanisation process and this through the prism of sustainability. This term covers two acceptances: a temporal continuity and a reference to sustainable development as understood by the Bruntdland Report. This article is founded on the hypothesis that small towns can play a role in an integrated approach to urbanisation (without a phenomenon of urban macrocephaly but with a balanced distribution of the population and jobs). Moreover, we believe that the PETR (urban space and rural space brought together) are the adequate scale to ensure economic, social and sustainable cohesion. To illustrate our remarks, we will base on the situation in the southern Massif central, an example of French interstitial spaces.